Distribution of inhalant allergies in pediatric patients presenting with allergic complaints in the Eastern Anatolia Region - Kilic, Mehmet; Taskin, Erdal (Edizioni Minerva Medica, 2016)
BACKGROUND: The objective of this study was to define the distribution of inhalant allergens in pediatric patients in whom sensitization was diagnosed with a skin prick test (SPT) who had presented with allergic complaints. In addition, the correlation between the inhalant allergens detected on the SPT and the patients' demographic features, diagnosis, and laboratory findings was defined. METHODS: A total of 1415 children among the 4056 patients who presented at a clinic in the Eastern Anatolia region with allergic complaints and who had undergone an SPT were included in this study. RESULTS: On the SPT, sensitization to grass pollens was found in 60.1%, cereals pollens in 57.2%, and Dermatophagoides farinae in 21.8% of the patients. Furthermore, on the SPT, incidence of asthma development was 3.96 times higher (odds ratio 3.96, 95% CI: 1.77-6.83; P=0.001) in patients who were allergic to Dermatophagoides farinae. CONCLUSIONS: In our study, differences were found in the study region compared to data from around the world and other regions in Turkey in terms of the distribution of allergies and variations in allergens in patients diagnosed due to variations in climate and plants.
Keywords: Allergens; Child; Asthma; Allergic rhinitis; Respiratory hypersensitivity